A band gap engineering for the modification in electrical properties of Fe3O4 by Cu2+ doping for electronic and optoelectronic devices applications - Saleem, Shahroz; Jameel, Muhammad Hasnain; Asma A. Alothman, Asma A. Alothman; Mayzan, Mohd Zul Hilmi; Yousaf, Talha; Ahmad, Muhammad Rehan; Ali, Asad; Zaman, Abid (Springer, 2023)
Magnetite nanoparticles (α-Fe3O4) were successfully prepared by a chemical co-precipitation technique. Modification in electrical properties of α-Fe3O4 by Cu2+ dopant for the modification in electrical properties was deliberated. As the Cu2+ dopant content increased from 5 to 10%, the average crystallite size decreased from 2.96 to 2.93 nm. The synthesized sample doped with 5% exhibited the porous nature and least agglomeration. The optical studies revealed that energy band gap increased from 1.76–1.83 eV by enhancing Cu2+ content from 5 to 10%. The electrical studies revealed that the electrical conductivity decreased from 4.04 × 10−5 to 9.17 × 10−6 ℧ cm−1 . The obtained consequences revealed that desired properties of Cu+2 doped Fe3O4 NPs can be obtained by controlling the substituting content in host material. The Fe3O4 NPs with Cu2+ doping exhibited higher electrical conductivity and become an excellent candidate for development of electronic and optoelectronic devices, such as, photodetector, sensors and energy storage devices.